Pendampingan Public Speaking Bagi Remaja Masjid Hidayatul Yaqin Desa Cen-Lecen Pamekasan - Abd Munib; Ahmad Baihaki; Matlani; Moh. Asy’ari (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2025)
Abstract This community service focuses on improving the Public Speaking skills of the youth at Masjid Hidayatul Yaqin, with the aim of enhancing the quality of preaching, boosting the youths' self-confidence, and increasing their involvement in religious activities. The issue faced is the low Public Speaking ability among the youth, which affects the quality of preaching and their participation in mosque activities. The approach used in this service program is Public Speaking training, utilizing direct practice, simulations, and intensive guidance. The results show a significant improvement in Public Speaking skills, which contributed to the enhanced quality of preaching at the mosque and active youth participation in religious activities. Additionally, the program has fostered the emergence of local leaders and new organizations that support the development of preaching activities. In conclusion, this training successfully created positive changes in communication skills, social engagement, and personal development of the youth, as well as strengthening social transformation in the community. Keywords: Skills, Public Speaking, Youth, Mosque. Abstrak Pengabdian masyarakat ini berfokus pada peningkatan keterampilan Public Speaking remaja di Masjid Hidayatul Yaqin, dengan tujuan untuk meningkatkan kualitas dakwah, kepercayaan diri remaja, serta keterlibatan mereka dalam aktivitas keagamaan. Isu yang dihadapi adalah rendahnya kemampuan berbicara di depan umum di kalangan remaja, yang mempengaruhi kualitas dakwah dan partisipasi mereka dalam kegiatan masjid. Pendekatan yang digunakan dalam pengabdian ini adalah pelatihan keterampilan berbicara di depan umum, dengan metode praktik langsung, simulasi, dan bimbingan intensif. Hasil pengabdian menunjukkan peningkatan signifikan dalam keterampilan Public Speaking, yang berpengaruh pada meningkatnya kualitas dakwah di masjid dan partisipasi aktif remaja dalam kegiatan keagamaan. Selain itu, kegiatan ini juga menciptakan pemimpin lokal dan lembaga-lembaga baru yang mendukung pengembangan kegiatan dakwah. Pelatihan ini berhasil menciptakan perubahan positif dalam kualitas komunikasi, keterlibatan sosial, dan perkembangan pribadi remaja, serta memperkuat transformasi sosial di masyarakat. Kata Kunci: Keterampilan, Public Speaking, Remaja Masjid.